Synthesis, characterization, and theoretical inhibitor study for (1e,1'e)-2,2'-thiobis(1-(3-mesityl-3-methylcyclobutyl)ethan-1-one) dioxime - Koparir, Pelin; Omer, Rebaz Anwar; Karatepe, Arzu; Ahmed, Lana Omer (TUBITAK, 2021)
In this study synthesized and characterization of (1E,1'E)-2,2'-thiobis(1-(3-mesityl-3-methylcyclobutyl)ethan-1-one) dioxime for both experimental and computational was reported. The solid-state FT-IR spectrum was observed in the range of 4000–400 cm-1 and CDCl3 solvents were used for1H and13C NMR analysis. The molecular geometry was calculated using the Density Functional Theory (DFT/B3LYP) method in the ground state with the 6-31G(d, p) basis sets. Vibrational assignments and chemical shifts have been measured theoretically and compared to experimental data. B3LYP/6-31G(d,p) applied on our title compound to found different parameters such as the energy of the highest occupied molecular orbital (EHOMO), the energy of the lowest unoccupied molecular orbital (ELUMO ), energy gap ( ?E = ELUMO-EHOMO) and the dipole moment (?) related to the corrosion efficacy of organic compounds whose molecular geometry and electronic properties are especially studied were calculated. Properties such as hardness (?), softness (?), electronegativity (?) values were computed using these measurement results to inhibitor activity. The fraction of transferred electrons (?N) was also calculated, which determined the interaction between the iron surface and the organic compounds. Corrosion inhibitor behavior can therefore be predicted without an experimental study. The findings of the calculations show good relation between organic-based corrosion inhibitors and quantum chemical parameters process. © 2021, TUBITAK. All rights reserved.
(1e,1'e)-2,2'-tiobis(1-(3-mesitil-3-metilsiklobutil)etan-1-on) dioksim için sentez, karakterizasyon ve teorik inhibitör çalışması
Keywords: DFT; Dioxime; Experimental Spectroscopy; Inhibitor activity; Theoretical spectroscopy